The flight of white-collars: Civil conflict, availability of medical service providers and public health. (January 2016) - Kıbrıs, Arzu; Metternich, Nils
Abstract: Civil conflicts devastate public health both in the short run and in the long run. Analyzing novel data sets that include yearly information on public health and the availability of health professionals across provinces in Turkey in the 1964–2010 period, we provide empirical evidence for our theoretical argument that a major mechanism through which civil conflicts exert their long term negative influences on public health is by discouraging medical personnel to practice in conflict regions. We also assess the effectiveness of certain policy measures that Turkish governments have tried out over the years to counteract this mechanism. Our results reveal that the long running civil conflict in Turkey has been driving away doctors and other highly trained medical personnel from conflict areas and that mandatory service requirements do help counteract this flight. Highlights: Civil conflicts drive medical personnel away from conflict areas. Presents empirical evidence from the long running civil conflict in Turkey. Mandatory service requirement for doctors prove to be an effective counter measure.